Crazy Heart - Cobb, Thomas; Hobbing, Erich; Horvitz, Marjorie (New York Harper Perennial, 2010)
At the age of fifty-seven$1 (Bliving a life riddled with ex-wives, one night stands, and daily diet of Jack Daniels$1 (BBad Blake is on his last legs. His ticker, his liver, even his pick-up truck are all giving him trouble. A renowned songwriter and (3z(Bpicker(3y (Bwho hasn$1 (Bt recorded in five years, Bad now travels the countryside on gigs that take him mostly to motels and bowling alleys. Enter Jean Craddock, a young journalist sent to interview him after a beautiful concert, and a tentative romance blooms. Can Bad stop living the life of a country-western song and tie a rope around his crazy heart?s
Keywords: English Literature; English Stories